Posttranscriptional regulation of cancer traits by HuR - Abdelmohsen, Kotb; Gorospe, Myriam (Wiley interdisciplinary reviews. RNA, 2010)
Cancer‐related gene expression programs are strongly influenced by posttranscriptional mechanisms. The RNA‐binding protein HuR is highly abundant in many cancers. Numerous HuR‐regulated mRNAs encode proteins implicated in carcinogenesis. Here, we review the collections of HuR target mRNAs that encode proteins responsible for implementing five major cancer traits. By interacting with specific mRNA subsets, HuR enhances the levels of proteins that (1) promote cell proliferation, (2) increase cell survival, (3) elevate local angiogenesis, (4) help the cancer cell evade immune recognition, and (5) facilitate cancer cell invasion and metastasis. We propose that HuR exerts a tumorigenic function by enabling these cancer phenotypes. We discuss evidence that links HuR to several specific cancers and suggests its potential usefulness in cancer diagnosis, prognosis, and therapy. Copyright © 2010 John Wiley & Sons, Ltd. This article is categorized under: RNA Turnover and Surveillance > Regulation of RNA Stability RNA in Disease and Development > RNA in Disease